Employing Mixed-Methods Explanatory Sequential Design: An Instructional Coaches Competencies in Malaysia’s Curriculum Aspect - Balang, Noel Jimbai; Balang, Noel Jimbai; Mahamod, Zamri; Buang, Nor Aishah (International Journal of Psychosocial Rehabilitation, 2020)
The instructional coaching program is established in the global education domain to facilitate teachers from the viewpoints of the curriculum, pedagogical and the practical. In every district of Malaysia, the instructional coaching program grants help to teachers through their coaches since 2012. In curriculum perspectives, the purposes of the Instructional Coaches (ICs) are promoted by knowledge and skills as being reported by the District Transformation Programme 3.0 (DTP 3.0). Accordingly, this research intended to recognise ICs’ level of competencies in curriculum aspects in Malaysia. In this investigation, a mixed-method explanatory sequential design was employed. Besides, before being analysed utilising SPSS version 23, the data were consolidated from 118 ICs throughout the nation in the form of questionnaires. Next, after manually analysed the meticulous interview, the output was adopted as the qualitative data. In the research, descriptive statistics including frequency, mean score, standard deviation and percentage were utilised. With a mean score of 4.23, sd=0.561 and by extensive interview, the research confirmed that ICs was proficient in the curriculum. Thus, it confirmed that the ICs’ competency level in curriculum awareness was at a high standard. Also, it suggested that in the curriculum regards of the subject being taught, ICs was accountable and expert. The conclusions of this research afford comprehension into ICs’ capacity to coach teachers in school and their system of quality teaching and learning (T&L). Furthermore, the teachers’ process to communicate and establish their struggles were determined by the school and social climate. Consequently, in an attempt to reach its purposes of assisting teachers, the instructional coaching program must be sufficiently appreciated and acknowledged by authorities of schools and education. Besides, in order to intensify what the coaches are trying to accomplish, environmental areas and possibilities for collaboration, certainly perform a vital position. In Malaysia’s context, this research’s authenticity is being highlighted as it is the pioneer study to examine the coaches’ competencies and experiences of who are actively engaging in the instructional coaching program for teachers. Accordingly, the authority must present assistance and collaboration to guarantee that ICs remains to be skillful in rendering quality coaching to teachers.